The JWST Extragalactic Mock Catalog: Modeling Galaxy Populations from the UV through the Near-IR over 13 Billion Years of Cosmic History - Williams, C; Curtis-Lake, E; Hainline, K; Chevallard, J; Robertson, B; Charlot, S; Endsley, R; Stark, D; Willmer, C; Alberts, S; Amorin, R; Arribas, S; et al. (American Astronimical Society, 2018)
We present an original phenomenological model to describe the evolution of galaxy number counts, morphologies, and spectral energy distributions across a wide range of redshifts ($0.2\lt z\lt 15$) and stellar masses $[\mathrm{log}(M/{M}_{\odot })\geqslant 6]$. Our model follows observed mass and luminosity functions of both star-forming and quiescent galaxies, and reproduces the redshift evolution of colors, sizes, star formation, and chemical properties of the observed galaxy population. Unlike other existing approaches, our model includes a self-consistent treatment of stellar and photoionized gas emission and dust attenuation based on the beagle tool. The mock galaxy catalogs generated with our new model can be used to simulate and optimize extragalactic surveys with future facilities such as the James Webb Space Telescope (JWST), and to enable critical assessments of analysis procedures, interpretation tools, and measurement systematics for both photometric and spectroscopic data. As a first application of this work, we make predictions for the upcoming JWST Advanced Deep Extragalactic Survey (JADES), a joint program of the JWST/NIRCam and NIRSpec Guaranteed Time Observations teams. We show that JADES will detect, with NIRCam imaging, 1000s of galaxies at z gsim 6, and 10s at z gsim 10 at ${m}_{{AB}}\lesssim 30$ (5σ) within the 236 arcmin2 of the survey. The JADES data will enable accurate constraints on the evolution of the UV luminosity function at z > 8, and resolve the current debate about the rate of evolution of galaxies at z gsim 8. Ready-to-use mock catalogs and software to generate new realizations are publicly available as the JAdes extraGalactic Ultradeep Artificial Realizations (JAGUAR) package.